Greed at the top. - Butalia, Urvashi (New Internationalist, 2010)
The article discusses the environmental and social impacts of economic growth and globalization in India where the number of wealthy people has increased. The economic conditions in India are described, particularly how the increase in wealth has changed the culture of India from an earlier time that the author remembers. The rise of consumer culture in India and an advertising industry is discussed as is an increase in the amount of garbage created.